2017
DOI: 10.22207/jpam.11.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Some Medicinal Plants of Kashmir, J&K, India

Abstract: The study was conducted to find out the activity of some medicinal plants against bacterial isolates. The bacterial isolates from milk samples of infected quarters of cows were investigated for in-vitro drug sensitivity by standard disc diffusion technique (Bauer et al., 1966). Cultural examination of milk samples was done by method described by Quin et al. (2004) in which predominant isolates were Staph. (55.55%), E. coli (22.22%), Strepto. agalactiae (16.66%) and other isolates as 5.5% and were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Adiantum has been reported for its various medicinal properties, specially antibacterial and antiviral, antifungal activities. Antibacterial activity of organic solvent extracts of different Adiantum species against P. aeruginosa (Thomas, 2017;Zhang et al, 2019), E. coli (Johnson et al, 2017) , K. pneumoniae (Johnson et al, 2017;Reshi et al, 2017), and S. aureus (Reshi et al, 2017;Thomas, 2017), Streptococcus agalactia (Reshi et al, 2017), Serratia marcescens (Thomas, 2017), Micrococcus lysodeikticus (Zhang et al, 2019), Bacterium paratyphosum B (Zhang et al, 2019), Bacillus subtilis have also been reported by various research groups.…”
Section: Plant Identi Ication and Relevance For Their Selectionmentioning
confidence: 91%
“…Adiantum has been reported for its various medicinal properties, specially antibacterial and antiviral, antifungal activities. Antibacterial activity of organic solvent extracts of different Adiantum species against P. aeruginosa (Thomas, 2017;Zhang et al, 2019), E. coli (Johnson et al, 2017) , K. pneumoniae (Johnson et al, 2017;Reshi et al, 2017), and S. aureus (Reshi et al, 2017;Thomas, 2017), Streptococcus agalactia (Reshi et al, 2017), Serratia marcescens (Thomas, 2017), Micrococcus lysodeikticus (Zhang et al, 2019), Bacterium paratyphosum B (Zhang et al, 2019), Bacillus subtilis have also been reported by various research groups.…”
Section: Plant Identi Ication and Relevance For Their Selectionmentioning
confidence: 91%
“…[99,100] Only two studies employed decoction for Borago officinalis leaves. [35,53] Zemmouri et al (2019) [35] reported 35.48 � 2.70 mg GAE/g of extract for phenolic compounds, 20.79 � 2.95 mg QE/g of extract for flavonoids, 10.88 � 0.18 mg R/g of extract for flavanols, 3.14 � 0.60 mg C/g of extract for tannins, and 0.09 � 0.01 mg CÀ 3-G/g of extract for anthocyanins in the B. officinalis leaves extract obtained with water/plant matérial of 50 : 1 (mL/g) for 20 minutes with occasional agitation. Levels of bioactive compounds, particularly phenolic compounds, flavonoids, and tannins, were lower compared to the ethanol extract obtained by maceration.…”
Section: Decoctionmentioning
confidence: 99%
“…The antibacterial properties of a methanolic extract of B. officinalis leaves using the agar diffusion method evidenced low antibacterial activity against Escherichia coli and Pseudomonas aeruginosa and moderate activity against Staphylococcus aureus. [56] In Reshi et al ( 2017), [53] various concentrations of the aqueous extract of B. officinalis leaves were tested on S. aureus, E. coli, S. agalactiae, and K. pneumoniae using the agar disk diffusion method (DDM), and cefuroxime as a positive control. This extract showed non-significant activity against the growth of the tested bacteria.…”
Section: Antibacterial Activity Of B Officinalis Leavesmentioning
confidence: 99%
See 2 more Smart Citations